Optimalisasi Pelaksanaan Kurikulum Al-Azhar Mesir Melalui Multaqo Muallimin Azhari Di Pondok Pesantren Diniyyah Al-Azhar Muara Bungo - Hasanah, Uswatun; Remiswal, Remiswal; Zalnur, Muhammad (Instructional Development Journal, 2025)
Abstract: This study is motivated by the implementation of the Al-Azhar Curriculum in Indonesia. Based on this background, the research aims to analyze the implementation of the Al-Azhar Curriculum in Madrasah Aliyah (MA) at Pondok Pesantren Diniyyah Al-Azhar Muara Bungo and to examine the role of the Multaqo Muallimin Azhari approach in optimizing the implementation of the Al-Azhar Curriculum in the same institution. This research falls under the category of a Case Study with a Qualitative approach. The findings indicate that the planning of the Al-Azhar Curriculum involves collaboration among the foundation board, school principal, vice principal of curriculum, coordinators, and teachers. The Multaqo Muallimin has proven to be effective in enhancing teacher competence through regular training, evaluation, and program mapping. The implementation of the Al-Azhar Curriculum has been shown to provide significant academic value and global competitiveness when carried out systematically and professionally. Abstrak: Penelitian ini dilatar belakangi oleh Pelaksanaan Kurikulum Al-Azhar di Indonesia. Berdasarkan latar belakang tersebut maka penelitian bertujuan menganalisis Pelaksanaan Kurikulum Al-Azhar Mesir di Madrasah Aliyah (MA) Pondok Pesantren Diniyyah Al-Azhar Muara Bungo dan menganalisis Multaqo Muallimin Azhari dalam mengoptimalkan pelaksanaan kurikulum Al-Azhar Mesir di Madrasah Aliyah (MA) Pondok Pesantren Diniyyah Al-Azhar Muara Bungo. Penelitian ini termasuk dalam kategori penelitian Studi Kasus (Case study research) dengan metode Kualitatif. Temuan peneliti dalam penelitian ini perencanaan dan pelaksanaan kurikulum Al-Azhar dilakukan kerja sama oleh pihak yayasan, kepala madrasah, waka kurikulum, koordinator, dan pendidik. Multaqo Muallimin bisa dikatakan efektif dalam meningkatkan kompetensi guru melalui pelatihan berkala, evaluasi, dan pemetaan program kerja. Kurikulum Al-Azhar Mesir ini terbukti memberi nilai tambah akademik dan kompetitif secara global bila diimplementasikan secara sistematis dan professional.